A Research and Critical Review of Masculinity in the Fictions of Tahir Afridi - Ali, Barkat; Ali, Anwar (sourcecoder, 2022)
Various movements and trends have influenced all genres of Urdu literature and these trends can be seen in the literature that has been created. The women's consciousness movement, which has spread its claws in Urdu literature with great force, has also presented a similar trend in literature with the same force. Man is convinced of the limits and limitations for himself in terms of different relationships and for women in terms of social status. It is called masculinity. This trend is very prominent in Urdu fiction and especially among the fiction writers of Khyber Pakhtunkhwa. In this regard, the different dimensions of masculinity can be seen in the above-mentioned fictional collection. In the subject under review, the same trend has been discussed in a research and critical manner.